Hubungan Tingkat Kepatuhan Minum Obat Pasien Hipertensi dengan Keberhasilan Terapi Pasien di Puskesmas Bergas - Ismi Astuti; Luluk Baristina; Maria Wahyuningsi Bita Satono; Meilinda Pratiwi Saktian; Setiaji Wisnu Wardana; Neli Diah Pratiwi (Pelantar Press, 2026)
Hypertension is a non-communicable disease that carries a risk of cardiovascular complications if not adequately controlled. One of the factors influencing the success of hypertension treatment is patients' adherence to antihypertensive medication. Low adherence to antihypertensive therapy may lead to poor treatment outcomes. Since hypertension can only be controlled rather than cured, long-term adherence to medication is essential. To determine the relationship between medication adherence and the success of antihypertensive therapy among hypertensive patients at Bergas Community Health Center. This study employed a quantitative, non-experimental analytic design with a cross-sectional approach. The study involved 41 hypertensive patients at Bergas Community Health Center. Data on medication adherence were collected using the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire, while data on therapeutic outcomes were obtained from patients’ medical records. Data were analyzed using the Chi-square correlation test with a significance level of p 0.05. The demographic characteristics of hypertensive patients at Bergas Community Health Center, Semarang Regency, showed that most participants were female (87.8%), aged over 60 years (75.6%), had suffered from hypertension for more than 5 years (61.0%), received single oral antihypertensive therapy (68.3%), and had comorbid conditions (53.7%). The majority of patients demonstrated a high level of medication adherence (90.2%), while therapeutic outcomes were categorized as successful in 73.2% of patients. The Chi-square correlation test revealed a statistically significant relationship between medication adherence and therapeutic success (p = 0.003; p 0.05). There is a significant relationship between medication adherence and the success of antihypertensive therapy among hypertensive patients at Bergas Community Health Center